ANALISIS PENGARUH PERTUMBUHAN PENJUALAN, PERPUTARAN TOTAL ASET, PERPUTARAN MODAL KERJA, DAN LIKUIDITAS TERHADAP PROFITABILITAS (Studi pada Perusahaan Manufaktur Sub Sektor Rokok yang Terdaftar di Bursa Efek Indonesia Periode 2013-2020) - Farida Dinda Fatharani; Asri Dwi Ariyani (IJMA (Indonesian Journal of Management and Accounting), 2022)
The quality and efficiency of managers are urgently needed in identifying factors that can affect profitability. A high profitability would signal a positive signal to a company of good corporate performance. This study aims to determine and analyze the effect of sales growth, total asset turnover, working capital turnover, and liquidity on profitability. The study is quantitative study using a causal associate study design. The population in this study is a sub-sector cigarette manufacturing company listed in Indonesia Stock Exchange period 2013-2020. The sampling techniques using purposive sampling method, so obtained 4 qualifying cigarette company as samples. The data analyzed method using multiple linier regression analysis. The results of this study indicate: (1) sales growth (Growth) has no significant effect on Profitability (ROA), (2) total asset turnover (TATO) has significant negative effect on profitability (ROA), (3) working capital turnover (WCTO) has no significant effect on profitability (ROA), and liquidity (CR) has no significant effect on profitability (ROA). Based on the result of the F test, it was found the F table value was 2,71 with a Sig. 0,000, which indicate that the independent variable has a simultaneous effect and can be used to predict the dependent variable. The value of R Square obtained is 0,710, which means that ROA is influenced by Growth, TATO, WCTO, and CR of 71% and the remaining 29% is explained by other variables such as leverage, corporate size, inventory turnover, accounts receivable turnover, or any other variable outside this model